Bright Luminescence in Three Phases—A Combined Synthetic, Spectroscopic and Theoretical Approach. (24th September 2021) - Dahlen, Milena; Hollesen, Eike H.; Kehry, Max; Gamer, Michael T.; Lebedkin, Sergei; Schooss, Detlef; Kappes, Manfred M.; Klopper, Wim; Roesky, Peter W.
Abstract: Combining phase‐dependent photoluminescence (PL) measurements and quantum chemical calculations is a powerful approach to help understand the influence of the molecular surroundings on the PL properties. Herein, a phosphine functionalized amidinate was used to synthesize a recently presented bimetallic gold complex, featuring an unusual charge separation. The latter was subsequently used as metalloligand to yield heterotetrametallic complexes with an Au‐M‐M‐Au "molecular wire" arrangement (M=Cu, Ag, Au) featuring metallophilic interactions. All compounds show bright phosphorescence in the solid state, also at ambient temperature. The effect of the molecular environment on the PL was studied in detail for these tetrametallic complexes by comparative measurements in solution, in the solid state and in the gas phase and contrasted to time‐dependent density functional theory computations. Abstract : The photoluminescence of Au‐M‐M‐Au (M=Cu, Ag, Au) „molecular wire" complexes was studied in detail by comparative measurements in solution, in the solid state and in the gas phase and contrasted to time‐dependent density functional theory computations.